Graphene Metal Nanoparticle-Composite - TAE YOUNG KIM; JONG PAL HONG (2017)
The present disclosure relates to a method of preparing a graphene metal nanoparticle-composite, including: preparing graphene by applying a shearing force to a first solution containing a graphite-based material and thus exfoliating the graphite-based material; preparing metal nanoparticles by applying a shearing force to a second solution containing a metal precursor, a capping agent, and a reducing agent; and physically combining the metal nanoparticles on the graphene by applying a shearing force to a third solution containing the graphene and the metal nanoparticles, and a graphene metal nanoparticle-composite prepared according to the method. 本发明涉及种石墨烯金属纳米粒子复合体的制备方法及利用所述制备方法制备的石墨烯金属纳米粒子复合体，所述制备方法包括以下步骤：通过对含有石墨系物质的第溶液施加剪切力而剥离所述石墨系物质来制备石墨烯；通过对含有金属前驱体、封端剂和还原剂的第二溶液施加剪切力来制备金属纳米粒子；以及通过对含有所述石墨烯和所述金属纳米粒子的第三溶液施加剪切力，使所述金属纳米粒子物理结合到所述石墨烯上。